Can ad‑hoc citizen observations be used to verify weather warnings? - Ric Crocker (Meteorologische Zeitschrift, 2018)
National weather warnings are a major part of a national meteorological organisation's remit. These warnings convey information about periods of severe weather which forecasters have deemed likely to have an impact on the public. The impacts are typically presented on a scale running from minor up to severe. Citizen submitted impact observations have been assessed to see whether they have the potential to verify the quality of weather warnings in terms of impact rather than meteorological accuracy. The observations are shown to provide useful information which can enhance subjective assessment of specific cases. It is demonstrated that this set of observations are not yet suitable for routine objective verification due to the sporadic nature of the data and the problem of missing correct negatives when forming contingency tables.